Real-time elastography for differentiation of breast lesions - Yılmaz, Ebru; Yılmaz, Ayhan; Aslan, Ahmet; İnan, İbrahim; Çalışkan Evren, Müjgan; Tekesin, Kemal (International Scientific Information Inc., 2017)
Backroung: To investigate the diagnostic performance of the elastography-based strain index ratio in the differential diagnosis of malignant and benign breast lesions. Material/Methods: Seventy-nine breast masses that were classified as BI-RADS category 3, 4, and 5 on B-mode ultrasonography (US) were further prospectively evaluated by real-time sonoelastography (RTE). To obtain an optimal cut-off value of the strain ratio for differentiating between malignant and benign breast lesions, RTE findings were compared with histopathology of core needle biopsy samples or with ultrasound follow-up data of the analyzed masses. Results: Seventy-nine breast lesions [BI-RADS category 3 (n=15), BI-RADS category 4 (n=34), and BI-RADS category 5 (n=30)] were classified as malignant (n=36) or benign (n=43). The mean strain index value was 6.59 +/- 3.44 (range 0.6-14) for malignant lesions and 2.79 +/- 2.16 (range 0.6-8.7) for benign lesions, respectively (p<0.05). As regards the detection of malignant lesions, US was characterized by sensitivity and specificity of 100% (CI 95%; 88-100) and 90% (CI 95%; 76-97), respectively. When an optimal value of the strain ratio (4.25) was obtained by ROC curve analysis, the sensitivity and specificity for diagnosing malignant lesions were 86% (CI 95%; 70-95) and 76% (CI 95%; 60-87), respectively. Conclusions: RTE can play an important role in the differentiation between malignant and benign breast masses, but it should be used in conjunction with ultrasonography.
WOS: 000417179500003
PubMed ID: 29657632
Keywords: Breast Diseases; Breast Neoplasms; Elasticity Imaging Techniques; Ultrasonography, Mammary